Comparative study of different phase change materials on the thermal performance of photovoltaic cells in Iraq's climate conditions - Majid Ahmed Mohammed; Bashar Mahmood Ali; Khalil Farhan Yassin; Obed Majeed Ali; Omar Rafae Alomar (Energy Reports, 2024)
The incident solar energy that impinges upon the photovoltaic cells undergoes a conversion process, resulting in the generation of electrical energy and conversion of absorbed energy into heat. This increase in temperature adversely affects the performance of the panel, leading to a decrease in its overall efficiency. This study examines the properties and performance of phase change materials, specifically paraffin wax, natural beeswax, and a combination of paraffin wax and beeswax, in comparison to a solar panel lacking any phase change substance. The experiment was conducted in the climatic conditions of Iraq, namely in the city of Hawija, located southwest of Kirkuk, during the summer of 2022. The prevailing environmental temperature throughout this period averaged 44 °C. The experiment involved comparing plate temperature, electrical power, and electrical efficiency. The results indicated that all the materials caused a decrease in the temperature of the board at the beginning of the experiment and for a short duration. Nevertheless, as the phase change material (PCM) undergoes melting, the dissipation of heat becomes unfeasible, resulting in a gradual increase in temperature. It was observed that there was a rise in temperature during the afternoon hours. According to the recorded data, the use of beeswax resulted in a decrease in temperature by 4 °C in comparison to the reference plate that did not incorporate phase change materials (PCM). Additionally, the efficiency of the photovoltaic (PV) system increased by 1% when compared to the PV Compared with PV (reference). The efficiency of the solar panel with beeswax ranged from 13% to 14%. According to the findings, the integration of phase-change materials with solar panels has been observed to effectively lower the temperature of the panels, hence enhancing their overall efficiency. Consequently, this approach represents a viable and advantageous choice.